Modelling indigenous knowledge creation as a living system - Tariq, Zaman; Kulathuramaiyer, Narayanan; Yeo, Alvin Wee; Falak, H. (Inderscience Enterprises Ltd., 2015)
Scientific community and organisations have to a large extent focused on indigenous knowledge management (IKM) as the management of a corpus of facts rather than management of and by a living system. Indigenous knowledge (IK) as a living system is much more reflective of and is closely tied to knowledge management (KM) processes and activities of indigenous people and their community systems. There is a need to explore the potential valueadds that can be derived from a more holistic modelling such assimilative knowledge creation systems. A living system is one that constantly creates new knowledge that is closely connected to day-to-day activities and social systems and is reflected upon before acceptance and assimilation. In this paper, the authors have proposed the extended tacit-implicit-explicit (TIE) model to conceptualise the indigenous communities' capabilities of harnessing creative expressions and indigenous wisdom. The objective of the study is to conceptualise the integrated model of community knowledge creation processes and its stages and use this as a basis to examine the potential role of information technology (IT). A case study on Bario-Long Lamai communities' information exchange and knowledge creation demonstrates the capabilities of the proposed model in enhancing knowledge management practices in indigenous communities.